Rekomendasi Pengembangan Desa Wisata di Penajam Paser Utara berbasiskan Focus Group Discussion dan Baseline Survey - Rismiyati, Fitri; Silano, Patrick; Ayu, Jati Paras; Imanez, Ladzina; Octavani, Vitha (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
The development of tourist villages is an effective way for the growth and development of the rural economy which has an impact on increasing people's welfare. This research aims to make a baseline survey in the development of Api-Api Tourism Village, Bangun Mulya Tourism Village, and Rozeline Flower Park. The method used for this research is qualitative with data triangulation with respect to data sources in verifying/re-examining existing research data, using a Participation Action Research (PAR) approach including baseline surveys, documentation, and Focus Group Discussions (FGD). . The data collected was then analyzed by assessing the feasibility study of the tourism business through 7 ADWI assessment categories. The result of this program is the feasibility of the Tourism Village in North Penajam Paser based on the survey (Baseline Survey) that has been conducted. The results of the Focus Group Discussion (FGD) 3 places in North Penajam Paser namely Api-Api Village, Bangun Mulya Village and Rozeline Flower Park have the potential to be developed to become tourist villages and tourist attractions, but need attention, assistance and guidance from the government as well as academics. Keywords: Tourism Village, Focus Group Discussion, Baseline Survey